Meta-Analysis the Effect of Urinary Tract Infection in Pregnant Women on Prematurity and Low Birth Weight - Wulandari, Rizqi Amalia; Budihastuti, Uki Retno; Murti, Bhisma (Journal of Maternal and Child Health, 2021)
Background: During pregnancy there are physiological changes associated with the pregnancy process that can cause urinary tract infections caused by the enlargement of the uterus, decreased urine flow through the ureters and decreased bladder tone during pregnancy. So that healthy pregnant women become vulnerable to serious complications in the urinary tract and will have an impact on the mother and baby who will be at great risk of causing premature birth and low birth weight. This study aims to estimate the magnitude of the effect of urinary tract infections in pregnant women on premature birth and low birth weight. Subjects and Method: This study is a systematic review and meta-analysis conducted with PRISMA flow diagrams. Search articles through journal databases including: Google Scholar, MEDLINE/PubMed, Science Direct, Spinger Link and Directory of Open Access Journal (DOAJ) by selecting articles published in 2005-2021. The keywords used were “Urinary Tract Infection Pregnancy” AND “Preterm Labor”, “Urinary Tract Infection Pregnancy” AND “Low Birth Weight”, “Urinary Tract Infection Pregnancy” AND “Preterm Labor” AND “Low Birth Weight” AND “adjusted Odds Ratio". Inclusion criteria included full-text articles, case-control study designs. The analysis used logistic regression with adjusted odds ratio. Eligible articles were analyzed using the Revman 5.3 application. Results: A total of 17 articles were reviewed in this study with a case control study design. A meta-analysis of 11 articles showed that urinary tract infections in pregnant women increased the risk of preterm delivery by 2.49 times compared with pregnant women without urinary tract infections (aOR = 2.49; 95% CI = 2.04 to 3.05; p<0.001), whereas 7 The article shows that urinary tract infections in pregnant women can increase the risk of increasing the risk of LBW by 1.54 times compared to pregnant women without urinary tract infections (aOR = 1.54; 95% CI = 1.24 to 1.91; p<0.001). Conclusion: Urinary tract infections increase the risk of preterm birth and low birth weight.